Practical field work at Pantu Oil Palm Plantation, Sebandi, Lundu - Chan, Margaret Kit Yok (Universiti Teknologi MARA, Sarawak, 2017)
The practical field work is part of the syllabus for the course work on Plantation Management Operation (AGR 615) for the Bachelor of Science (Hons) Plantation Technology and Management course offered by the Faculty of Plantation and Agroteknology in Samarahan campus. The field work at Pantu Small Holder Oil Palm Plantation provided the platform to assess the ability of Part 5 students to evaluate and handle plantation operational activities that contribute to managerial effectiveness. Thirty students accompanied by Associate Professor Dr. Margaret Chan went on the field trip on 12 June 2017.